Preliminary characterization of PEGylated nanostructured lipid carriers as potential drug delivery system - A. A. Ugwu; P. O. Nnamani; A. A. Attama (Journal of Applied Sciences and Environmental Management, 2024)
This study is a preliminary characterization of PEGylated nanostructured lipid carriers as potential drug delivery system using appropriate standard methods.  DSC traces showed that PEG 4000 was the most crystalline of all the lipids and Softisan® 154 was the least crystalline due to high enthalpy (-36mW/mg) and low enthalpy (-8.9 mW/mg) respectively. It was noticeable that the endothermic peak heights of PEGylated lipid matrix became smaller compared with the original starting lipid. All demonstrated good potentials for use as nanostructured lipid carrier drug delivery system but LMA, LMB and LMC turned to be the preferred in other of better thermal activity. SEM analysis revealed evidence of coarse structure amorphous than the individual lipidic systems. By implication showed increase drug loading capacity, it follows that that PEGylated nanostructured might be employed as NLCs carriers to serve as alternative transdermal delivery systems to improve the solubility of some poorly soluble drugs.